Cry46Ab from Bacillus thuringiensis TK-E6 is a new mosquitocidal toxin with aerolysin-type architecture. (August 2017) - Hayakawa, Tohru; Sakakibara, Akira; Ueda, Sho; Azuma, Yoshinao; Ide, Toru; Takebe, So
Abstract: Cry46Ab is a Cry toxin derived from Bacillus thuringiensis TK-E6. Cry46Ab is not significantly homologous to other mosquitocidal Cry or Cyt toxins and is classified as an aerolysin-type pore-forming toxin based on structural similarity. In this study, the potency of Cry46Ab was assessed for its potential application to mosquito control. A synthetic Cry46Ab gene, cry46Ab-S1, was designed to produce recombinant Cry46Ab as a glutathione- S -transferase fusion in Escherichia coli . Recombinant Cry46Ab showed apparent toxicity to Culex pipiens larvae, with a 50% lethal dose of 1.02 μg/ml. In an artificial lipid bilayer, Cry46Ab activated by trypsin caused typical current transitions between open and closed states, suggesting it functions as a pore-forming toxin similar to other Cry and Cyt toxins. The single-channel conductance was 103.3 ± 4.1 pS in 150 mM KCl. Co-administration of recombinant Cry46Ab with other mosquitocidal Cry toxins, especially the combination of Cry4Aa and Cry46Ab, resulted in significant synergistic toxicity against C. pipiens larvae. Co-administration of multiple toxins exhibiting different modes of action is believed to prevent the onset of resistance in insects. Our data, taken in consideration with the differences in its structure, suggest that Cry46Ab could be useful in not only reducing resistance levels but also improving the insecticidal activity of Bt-based bio-insecticides. Graphical abstract: Highlights: A synthetic cry46Ab-S1 gene was designed and recombinant Cry46Ab was produced as a GST fusion in Escherichia coli. Recombinant Cry46Ab is highly toxic to Culex pipiens larvae, with a 50% lethal dose of 1.02 (0.87–1.22) μg/ml. Cry46Ab formed pore in an artificial lipid bilayer with single-channel conductance of 103.3 ± 4.1 pS in 150 mM KCl. Co-administration of Cry46Ab with Cry4Aa resulted in significant synergistic toxicity against Culex pipiens larvae. Cry46Ab may be useful in not only reducing resistance but also improving insecticidal activity of Bt-based insecticides.